Pendekatan Ontologis Dalam Pembelajaran Akidah Di Raudhatul Athfal - Marlina, Elvia Hani; Nugraha, Mulyawan Safwandy (Peneliti.net, 2025)
This study explores the application of the ontological approach in learning akidah in Raudhatul Athfal (RA) and its impact on children's spiritual understanding and faith development. Traditional learning approaches in most RA generally emphasize memorization, leaving less room for children to understand the concept of faith in depth. This study aims to evaluate the extent to which an ontological approach can deepen children's understanding of faith by promoting reflection and essential understanding. Using a qualitative approach with a case study design at HALIMAH Kindergarten, this study found that the ontological approach, which focuses on the essence and meaning of faith, plays an important role in shaping children's personal faith. The results show that this approach helps children to internalize religious values in a more meaningful way, not just memorization but also deep understanding.